Jordan : 2010 Article IV Consultation-Staff Report and Public Information Notice. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The economy of Jordan was affected by the global crisis. Lower commodity prices helped improve Jordan's external position. Effective banking supervision has strengthened the capacity of Jordanian banks to withstand shocks. The authorities have implemented prudent fiscal and monetary policies. The medium-term fiscal strategy should be supported by a number of institutional reforms. The fixed exchange rate regime remains important for financial stability. Bank regulation and supervision should continue to focus on preventing excessive risk-taking.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet